Plant receptor-like kinase signaling through heterotrimeric G-proteins - Pandey, Sona (J Exp Bot, 2020)
Heterotrimeric G-proteins regulate multiple aspects of plant growth, development, and response to biotic and abiotic stresses. While the core components of heterotrimeric G-proteins and their basic biochemistry are similar in plants and metazoans, key differences exist in their regulatory mechanisms. In particular, the activation mechanisms of plant G-proteins appear diverse and may include both canonical and novel modes. Classical G-protein-coupled receptor-like proteins exist in plants and interact with Gα proteins, but their ability to activate Gα by facilitating GDP to GTP exchange has not been demonstrated. Conversely, there is genetic and functional evidence that plant G-proteins interact with the highly prevalent receptor-like kinases (RLKs) and are phosphorylated by them. This suggests the exciting scenario that in plants the G-proteins integrate RLK-dependent signal perception at the plasma membrane with downstream effectors. Because RLKs are active kinases, it is also likely that the activity of plant G-proteins is regulated via phosphorylation/dephosphorylation rather than GTP–GDP exchange as in metazoans. This review discusses our current knowledge of the possible RLK-dependent regulatory mechanisms of plant G-protein signaling in the context of several biological systems and outlines the diversity that might exist in such regulation.